Studies on the flies producing cutaneous myiasis in domestic animals in Trichur - Subramanian H (Department of Parasitology, College of Veterinary and Animal Sciences, 1978)
A detailed study on the incidence of cutaneous myiasis among domestic animals in Trichur, the morphology and biology of the causative flies and the efficacy of indigenous oils and chemicals as repellents against these flies were undertaken. Cutaneous myiasis was found common among domestic animals in Trichur during the months of October to May, the maximum number being, during January to March. The cases were observed in cattle, buffaloes, goats and dogs. The most common causative fly was Chrysomyia bezziana, but other flies such as Chrysomyia megacephala, Chrysomyia rufifacies and Lucilia cuprina were also observed. In cattle and buffaloes, the lesions were noted mostly in vulval lips and nasal septa where as in goats and dogs the cases were observed on the body skin. The flies of Chrysomyia megacephala, Chrysomyia rufifacies, Chrysomyia nigripes, Lucilia cuprina and Sarcophaga ruficornis were reared in the laboratory to study their morphology and biology. The larvae of Lucilia cuprina and Sarcophaga ruficornis were smooth. Chrysomyia bezziana, Chrysomyia megacephala and Chrysomyia nigripes were spiny and Chrysomyia rufifacies hairy. Chrysomyia rufifacies had the shortest life cycle period of 16 days and Sarcophaga ruficornis had the longest of 26 days. Lucilia cuprina could be reared in the laboratory for 71 days. The invitro development of the larvae, the development of the pupae and the process of fly emergence of Chrysomyia megacephala and Sarcophaga ruficornis were studied in detail. Among the fly repellents tested, lemongrass oil proved to be the best one in possessing fly repellent potentially followed by camphor in oil and Eucalyptus oil against blowflies and Sarcophaga species. Kerosine oil and Turpentine oil possessed the maximum larvicidal action on the larvae of Chrysomyia megacephala and Sarcophaga ruficornis. Turpentine oil and pine oil possessed excellent ovicidal action on Lucilia cuprina eggs even on smearing.